Regulation of Trade in Communication Services in the Framework of the General Agreement on Trade in Services (GATS) in Indonesia: A Study on the Practice of Perum LKBN Antara - Frislidia Fatria; Zainul Daulay; Delfiyanti (Ekasakti Journal of Law and Justice, 2026)
The GATS, or General Agreement on Trade in Services, is set out in Annex 1B of the WTO Agreement, which sets out the rules and principles that member states must follow in trade in communication services. Perum LKBN Antara assigned by the State, based on article 1 paragraph 3 of the GATS, the services provided by Antara fall within the scope of the exemption of services provided in the implementation of government authority, namely services that are not supplied commercially or competitively. Antara's business practices are also subject to gradual liberalization as stipulated in Articles IV and XIX of the GATS, namely communication services are adjusted to national policy objectives. The formulation of the problem in this thesis is how to apply the principles in GATS to the communication services sector in the laws and regulations in Indonesia, how to implement the principles of GATS in Indonesia, especially in the communication services sector in relation to the LKBN Antara Regulation in the face of the liberalization of the communication services sector. The purpose of the research is to review and analyze the regulation of trade in services within the framework of GATS in the communication sector as well as to examine and analyze the practice of trade in communication services in Indonesia through Perum LKBN Antara. This study uses an empirical juridical approach with primary data through interviews with officials of Perum LKBN Antara, and secondary data obtained from the study of legal documents and related literature. The practice of Perum LKBN Antara and regulating its rights and obligations is Law Number 7 of 2014 concerning Trade, Law (UU) Number 1 of 2024 concerning Information and Electronic Transactions (ITE Law), and Article XVI and Article XVII of the GATS regulating the service sector as well as Law of the Republic of Indonesia No. 40 of 1999 concerning the Press, Law Number 32 of 2002 concerning Broadcasting,  Government Regulation Number 40 of 2007 concerning Public Companies (Perum) of the Antara National News Agency.